Peregrinările institutului - I. Oprişan (Revista de Istorie și Teorie Literară)
It is a record of the changings of the institutional residences 7 times during 4 decades, until the final settlement in the House of the Academy. The article describes the episodes of the successive removals ordered by arbitrary decisions of the Party and State authorities in the communist regime.